Adenoviral vector-mediated gene therapy for gliomas: coming of age. (September 2014) - Castro, Maria G; Candolfi, Marianela; Wilson, Thomas J; Calinescu, Alexandra; Paran, Christopher; Kamran, Neha; Koschmann, Carl; Moreno-Ayala, Mariela A; Assi, Hikmat; Lowenstein, Pedro R
<x xml:space="preserve">Abstract</x> Introduction: Glioblastoma multiforme (GBM) is the most common primary brain tumor in adults and it carries a dismal prognosis. Adenoviral vector (Ad)-mediated gene transfer is being developed as a promising therapeutic strategy for GBM. Preclinical studies have demonstrated safety and efficacy of adenovirus administration into the brain and tumor mass in rodents and into the non-human primates' brain. Importantly, Ads have been safely administered within the tumor resection cavity in humans. Areas covered: This review gives background on GBM and Ads; we describe gene therapy strategies for GBM and discuss the value of combination approaches. Finally, we discuss the results of the human clinical trials for GBM that have used Ads. Expert opinion: The transduction characteristics of Ads, and their safety profile, added to their capacity to achieve high levels of transgene expression have made them powerful vectors for the treatment of GBM. Recent gene therapy successes in the treatment of retinal diseases and systemic brain metabolic diseases encourage the development of gene therapy for malignant glioma. Exciting clinical trials are currently recruiting patients; although, it is the large randomized Phase III controlled clinical trials that will provide the final decision on the success of gene therapy for the treatment of GBM.